Circular business model evolution: Stakeholder matters for a self‐sufficient ecosystem. (21st February 2021) - Moggi, Sara; Dameri, Renata Paola
Abstract: Food waste is a key issue in the circular economy. A circular ecosystem results from the contributions of various stakeholders; however, the claims and value propositions of these stakeholders can differ, hampering long‐term sustainability of the ecosystem. This study analyses the case of RiCibo, a circular ecosystem based in Genoa, Italy. RiCibo collects surplus food and redistributes it to the needy in the local community. The study examines the conditions that facilitated RiCibo's evolution from a simple project to a circular self‐sufficient ecosystem characterised by a co‐designed circular business model with a broad range of stakeholders. The results show that sharing people, infrastructure and knowledge, together with mutual trust among stakeholders, are the preconditions of a circular ecosystem. Long‐term continuity depends on additional tools that enhance financial self‐sufficiency, namely, participative governance, a co‐designed circular business model, accountability, frequent engagement, local actions and the development of advocacy power.